2003
DOI: 10.1897/1551-5028(2003)022<0342:iodsow>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Sodium on Waterborne Copper Toxicity in Rainbow Trout, Oncorhynchus Mykiss

Abstract: Juvenile rainbow trout were fed diets containing control (0.26 mmol/g) or elevated (1.3 mmol/g) dietary Na+ in combination with either background (19 nmol/L) or moderately elevated levels (55 or 118 nmol/L) of waterborne Cu for 21 d. Unidirectional waterborne Na+ uptake rates (measured with 22Na) were up to four orders of magnitude higher than those of Cu (measured with 64Cu). Chronic exposure to elevated dietary Na+ alone or in combination with elevated waterborne Cu decreased whole-body uptake rates of water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Specifically, exposure of freshwater fish to elevated dietary NaCl suppresses branchial Na + uptake (Smith et al 1995;Kamunde et al 2003;, increases diffusive Na + efflux via the gills (Smith et al 1995;Pyle et al 2003), and increases renal Na + excretion (Salman and Eddy 1987). Our data are consistent with these findings.…”
Section: Role Of the Gut In Na + Homeostasis During Exposure To Elevasupporting
confidence: 85%
See 2 more Smart Citations
“…Specifically, exposure of freshwater fish to elevated dietary NaCl suppresses branchial Na + uptake (Smith et al 1995;Kamunde et al 2003;, increases diffusive Na + efflux via the gills (Smith et al 1995;Pyle et al 2003), and increases renal Na + excretion (Salman and Eddy 1987). Our data are consistent with these findings.…”
Section: Role Of the Gut In Na + Homeostasis During Exposure To Elevasupporting
confidence: 85%
“…Consequently, sampling after a substantial period of starvation (e.g., Kamunde et al 2003) is unlikely to capture these apparently transient changes in tissue Na + levels.…”
Section: Whole-body and Tissue Cu And Na + Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These indirect effects would raise whole cell Cu content as Na + o declines, giving the impression of apparent Na + o -dependent Cu uptake. In vivo, there may also be systemic Na + -dependent modulation of Cu uptake (systemic Na + effects on Cu uptake by trout gills; Kamunde et al, 2003;Pyle et al, 2003).…”
Section: Dids (Normal CLmentioning
confidence: 99%
“…The explanation for the marginal effect in freshwater killifish may be a matter of threshold. In critically reviewing a number of saltfeeding papers on salmonids (Smith et al, 1995;Kamunde et al, 2003;Pyle et al, 2003;Niyogi et al, 2006), Wood and Bucking (Wood and Bucking, 2011) concluded that the threshold for increases in branchial Na + efflux rate lay above a salt concentration of 1270μmolNa It would be interesting to test whether the same considerations apply to uptake and retention of Cl -from high-and low-salt diets in the freshwater killifish. However, cost considerations precluded repeating the experiment with low-salt diets labelled with 36 Cl -.…”
Section: Low-salt Versus High-salt Dietsmentioning
confidence: 99%